2021
DOI: 10.1002/ejoc.202001496
|View full text |Cite
|
Sign up to set email alerts
|

C−H Activation and Cross‐Coupling of Acyclic Aldonitrone

Abstract: Palladium‐catalyzed activation of C(sp2)−H bond in a readily E,Z‐isomerizable aldonitrone, bearing an ester group at the C terminus, enabled its cross‐coupling with a variety of aryl and heteroaryl bromides to give ketonitrones, including products with functional groups not compatible with the classical nitrone synthesis via condensation with hydroxylamines. The reactions proceeded with very high (usually complete) E selectivity. The key to obtaining good yields of the cross‐coupling products was the use of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Loska and co-workers disclosed in 2021 that addition of bromobenzene to N-(2-ethoxy-2oxoethylidene)methanamine oxide using Pd(OAc) 2 / PPh 3 catalyst and K 2 CO 3 in toluene required carboxylic acid additive. [40] Its structure had a dramatic effect on the efficiency (Scheme 5a), the best result arising with the bulky tri(cyclohexylmethyl)acetic acid previously used by Tsuji, Fujihara and co-workers (see below). [41] The high selectivity towards the E cross-coupling product as well as the determinant role of the carboxylate ligand led Loska's team to assume a mechanism involving coordination of the nitrone oxygen to the phenylpalladium complex as depicted in 5bA (Scheme 5b).…”
Section: Intermolecular Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loska and co-workers disclosed in 2021 that addition of bromobenzene to N-(2-ethoxy-2oxoethylidene)methanamine oxide using Pd(OAc) 2 / PPh 3 catalyst and K 2 CO 3 in toluene required carboxylic acid additive. [40] Its structure had a dramatic effect on the efficiency (Scheme 5a), the best result arising with the bulky tri(cyclohexylmethyl)acetic acid previously used by Tsuji, Fujihara and co-workers (see below). [41] The high selectivity towards the E cross-coupling product as well as the determinant role of the carboxylate ligand led Loska's team to assume a mechanism involving coordination of the nitrone oxygen to the phenylpalladium complex as depicted in 5bA (Scheme 5b).…”
Section: Intermolecular Reactionsmentioning
confidence: 99%
“…Loska and co‐workers disclosed in 2021 that addition of bromobenzene to N ‐(2‐ethoxy‐2‐oxoethylidene)methanamine oxide using Pd(OAc) 2 /PPh 3 catalyst and K 2 CO 3 in toluene required carboxylic acid additive [40] . Its structure had a dramatic effect on the efficiency (Scheme 5a), the best result arising with the bulky tri(cyclohexylmethyl)acetic acid previously used by Tsuji, Fujihara and co‐workers (see below) [41] .…”
Section: Formation Of C(sp2)−c(sp2) Bondsmentioning
confidence: 99%
“… 20 We have recently disclosed a Pd-catalyzed reaction for the C–H activation of aldonitrones bearing an ester group to access various aryl ketonitrones ( Scheme 1 A). 21 In this approach, a reaction pathway has been proposed in which the nitrone oxygen atom serves as the directing group, facilitating the cross-coupling process. Accordingly, our envisioned strategy toward benzocyclobutenone-derived nitrones, which we term benzocyclobutenitrones (BCBn), is based upon palladium-catalyzed cyclization of bromoaryl-substituted aldonitrones ( Scheme 1 C).…”
mentioning
confidence: 99%
“…Their efficiency in the formation of four-membered rings of BCBs via C­(sp 3 )–H activation is well-documented. ,, Concerning coupling of two C­(sp 2 ) carbon atoms, the 2010 seminal report of Martin et al indicated that benzocyclo­butenones could be obtained by simple palladium-catalyzed cyclization of haloaryl-containing aldehydes (Scheme B) . We have recently disclosed a Pd-catalyzed reaction for the C–H activation of aldonitrones bearing an ester group to access various aryl ketonitrones (Scheme A) . In this approach, a reaction pathway has been proposed in which the nitrone oxygen atom serves as the directing group, facilitating the cross-coupling process.…”
mentioning
confidence: 99%